Motivational patterns of internet-addiction in members of anonymous online communities - Chugunov, V. V.; Horodokin, A. D.; Skripnik, A. S.; Чугунов, Вадим Віталійович; Городокін, Антон Дмитрович; Скрипник, Анна Сергіївна; Чугунов, В. В.; Городокин, А. Д.; Скрипник, А. С. (My University, 2016)
In order to perform comparative analysis and to develop typology of pathological internet-specific patterns of communication in individuals with personologic-determined forms of internet-addiction and the participants of anonymous online communities, 80 respondents suffering from Internet-addiction according to the results of questionnaire Internet-UDIT were surveyed, among them 40 members of anonymous Internet community, identifying themselves as “Hikikomory”, which declare social autoisolation. Such pathoconative communicative stereotypes were revealed: formallycommunicative, compulsive, autistic, utilitarian-communicative, alternativelymotivational, creatively-narcissistic and recreational, their specifi c characteristics and denotation were described. З метою порівняльного аналізу і формування типології патологічних інтернет-специфічних комунікативних паттернів у осіб з персонологічно-детермінованими формами інтернет-залежності та учасників анонімних інтернет-спільнот було обстежено 80 респондентів, що страждають інтернет-залежністю згідно результатів опитувальника Internet-UDIT, серед яких 40 членів анонімної інтернет-спільноти, які ідентифікують себе як «Хікікоморі», що декларують соціальну аутоізоляцію. Виявлено такі патоконативні комунікативні стереотипи: формально-комунікативний, компульсивний, аутистичний, утилітарно-комунікативний, альтернативно-мотиваційний, креативно-нарцисичний, рекреаційний, подано їх денотації та ракурсні характеристики.
Мотиваційні паттерни інтернет-аддикції у членів анонімних інтернет-спільнот
Мотивационные паттерны интернет-аддикции у членов анонимных интернет-сообществ
Keywords: internet addiction; hikikomori; pathoconative communicative stereotypes; інтернет-залежність; хікікоморі; патоконативні комунікативні стереотипи; интернет-зависимость; хикикомори; патоконативные коммуникативные стереотипы